Investigation into the characteristics of proton exchange membrane fuel cell‐based power system. Issue 3 (1st May 2016) - Alrewq, Mohmmad; Albarbar, Alhussein
Abstract : Fuel cells (FCs) use hydrogen as their prime fuel source, which promotes them as one of the attractive options for clean energy generators. Though they have been around for some time, their characteristics are not yet fully understood. This study offers a thorough investigation into the characteristics of proton exchange membrane (PEM) type of FCs based power system. This study first presents a concise explanation of the working principles of the PEM electrolyser and FCs supported by novel modelling using MATLAB. The simulation results are then validated by a series of experiments carried out on operational 500 mW FC followed by detailed performance parameters of such type of FCs. Parameters affect the efficiencies of each part of the system are investigated and the total system's efficiency is then calculated. The efficiency of the electrolyser and PEM FC was found to be 85 and 60%, respectively. Polarisation curve has been used in order to evaluate FC's performance. From the polarisation curve, it is noted the efficiency of the FC increases with increasing pressure and temperature. The activation losses are reduced when the temperature increased. Moreover, the mass transfer is enhanced toward reducing the PEMFC's resistance.